The Prevalence of Alprazolam Uses in Geriatric Patients at Dr. Mohammad Hoesin Hospital Palembang - Yohanes Febrianto; Sutomo Tanzil; Theodorus Parulian (Intelektual Pustaka Media Utama, 2016)
One of the most frequently prescribed drugs in geriatric patients is a benzodiazepine, especially a short-acting such as alprazolam. Unfortunately, alprazolam is oftenly used inappropriately because this drug has a short acting effect. Geriatric patients are more sensitive to this drug that can lead to the dependence. However, there is still lack of data on the use of this drug in geriatric patients. The aim of this study was to determine the prevalence of the use of alprazolam. A drug utilization study has been done for 2 months through analysis of patient’s medical records in the internal medicine ward at RSMH Palembang from June 1st, 2012 to May 31st, 2013. There were 25 out of 1634 patients receiving alprazolam, but only 23 patients whose data were obtained from the available medical records. Prevalence of alprazolam use was 1.408%. Based on gender, the prevalence was 1.798% in female and 1.09% in male patients. Proportion by age group was 91.3%, 8.7% and 0% in age group 60-74 years, 75-90 years and over 90 years, respectively. Based on the job, the population study comprised of the housewive (52.1%), unemployment (39.1%), and entrepreneur and farmer (4.3% together). The indication of usage was atheroscerotic heart disease, diarrhoea and gastroenteritis of presumed infectious origin, unspecified gastritis, and thyrotoxic heart disease. In other words, it could be said that the usage of alprazolam was inappropriate.